2021
DOI: 10.1038/s41598-021-98140-3
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of new undergraduate students before and after COVID-19 in China

Abstract: The purpose of this study was to examine the changes in severity of anxiety and depression symptoms, stress and sleeping quality after three months of mass quarantine for COVID-19 among undergraduate fresh students compared to their pre-COVID-19 measures. We used participants from the Chinese Undergraduate Cohort (CUC), a national prospective longitudinal study to examine the changes in anxiety and depression symptoms severity, stress and sleep quality after being under mass quarantine for three months. Wilcox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…However, with the protective effect of resilience, psychological symptoms were assuaged, and people recovered slowly to a new fragile balance. This may be why some reports have found that COVID-19 lockdowns did not influence mental health ( 40 ) and that there was no difference between Chinese students before and after being isolated on campus ( 41 ). Of particular interest is the fact that when the lockdown was implemented again, various psychological symptoms recurred, which is reflected in the results of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the protective effect of resilience, psychological symptoms were assuaged, and people recovered slowly to a new fragile balance. This may be why some reports have found that COVID-19 lockdowns did not influence mental health ( 40 ) and that there was no difference between Chinese students before and after being isolated on campus ( 41 ). Of particular interest is the fact that when the lockdown was implemented again, various psychological symptoms recurred, which is reflected in the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis concluded that COVID-19 lockdowns did not impact mental health ( 40 ). A longitudinal study on the mental health status of Chinese college students also found no difference before and after being isolated on campus due to the COVID-19 pandemic ( 41 ). One possible reason for the discrepancies in the results of various studies may be that isolation and lockdown were not clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…While few studies to date have examined the effect of coping appraisal (e.g., sense of control) on the COVID-19-induced psychic anxiety ( 28 ), the underlying mechanism for explaining this effect is underexplored. Further, previous studies have supported the association of positive PFC and EFC strategies with low levels of COVID-19-induced anxiety among college students during the COVID-19 pandemic ( 19 , 20 ), and the prevention of mental health deterioration in college students by scientific coping methods (e.g., quarantine policy) ( 29 ), suggesting a possible beneficial role of coping strategies in coping appraisal and psychic anxiety. Chen and Liang ( 30 ) further confirmed that coping appraisal influences users’ behavioral intention through the mediations of PFC and EFC strategies.…”
Section: Introductionmentioning
confidence: 73%
“…Second, we reveal the roles of two different forms of coping strategies in mediating the relationship between perceived threat avoidability and psychic anxiety based on the cognitive appraisal theory. The studies that have been conducted on the mediating mechanisms of coping strategies in COVID-19 threat and anxiety may focus on external ones, such as quarantine strategies ( 29 ), and lack the exploration of internal cognitive coping strategies. Whereas in studies of internal cognitive coping strategies, although existing studies have investigated the direct effects of coping strategies on anxiety ( 19 , 20 ), little is known about the antecedents of EFC and PFC coping strategies and whether these two types of coping strategies mediate the relationship between perceived threat avoidability and psychic anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rizvi and the authors reported 40.9% prevalence of depression among the students of Pakistan [24]. The other reported prevalence of depression were 37% in Malaysia, 43.7% in India, 68.5% in Hong Kong; 27.1% in Turkey, nearly fifty percent in Saudi Arabia, more than three quarter in Egypt, more than one fifth present in the USA and Australia [25], [26], [27], [28], [29], [30], [31], [32]. The anxiety rates were reported fifty percent in Turkey and Hong Kong, more than a quarter in USA and Australia, and more or near about three quarter in Pakistan, India, Saudi Arabia, Egypt and Malaysia [25], [26], [27], [28], [29], [30], [31], [32].…”
Section: Discussionmentioning
confidence: 99%